Termoestatística do movimento superamortecido de partículas interagentes - Silva, George Frederick Tavares da (2013)
The Fokker-Planck equations of nonlinear - EFPNL are differential equations able to describe macroscopic physical and chemical systems that have some type of anomalous diffusion. Examples of applications of scientific and technological importance, we may cite the case of transport in porous media, the growth dynamics of surfaces, diffusion of polymerlike breakable micelles and the dynamics of interacting vortices in type II superconductors. For the latter, it is known that the vortex motion causes power dissipation, and the interaction between them can be represented by a modified Bessel function type. Therefore, in order to model vortices in superconductors, we study the overdamped motion of interacting particles in contact with a thermal reservoir at temperature T, using the same type of interaction for vortices. We show, by means of the nonlinear Fokker-Planck equations formalism, that there is an association of the system under study, in the temperature limit T = 0, with the generalized Tsallis statistics. To prove this direct relation, we use the well-known H theorem and its generalizations, which allows an unambiguous relationship between the generalized entropy function with EFPNL. We show that even for relatively high temperatures, the system should be better represented by the Boltzmann-Gibbs standard statistical, since the distribution function of particles in the steady state, has the form of a Gaussian. In addition to the analytical results for the distribution function, numerical results for overdamped motion of interacting particles were obtained by molecular dynamics with the addition of white noise (additive) thus confirming the theoretical results.